The Role of Oil Industry in The Socioeconomic Status in Iraq - Rasheed, Suhad A. (Research Parks Publishers, 2023)
This research is aimed at clarefying the role of oil industries in supporting the socioeconomical life in Iraq. The oil industry plays a vital role in the socioeconomic fabric of oil-producing countries like Iraq, where its dominance in the economy is driven by oil exports and associated industries. This study spotted the light on the influence of the oil industry on Iraq's socioeconomic landscape, specifically its impact on unemployment, poverty, education, and health sectors. By analyzing the data collected from reputable sources, such as the World Bank and official government reports, spanning the period from 2003 to 2021, this research conducted a comprehensive understanding of the relationship between the proportion of the oil industry in the Gross Domestic Product (GDP) and its effects on these key indicators. The findings of this study is presenting the overall analysis of the role of oil industry in enhancing the socioeconomic life in Iraq, and preparing valuable insights for policymakers and stakeholders in making informed decisions, promoting sustainable economic growth, and enhancing the overall quality of life for the people of Iraq.